Method for preparing perovskite photocatalytic reduction material from titanium-containing blast furnace slag
By crushing, grinding and acid-base combined leaching of titanium-containing blast furnace slag, perovskite photocatalytic materials with crystal-branched structures were prepared, and microwave baking technology was used to regulate the energy-changing structure of the materials, which solved the problem of low efficiency in the existing technology that it is difficult to effectively utilize titanium-containing blast furnace slag and traditional photocatalytic CO2 conversion technology, and achieved efficient CO2 photocatalytic reduction and improvement of environmental protection performance.
Patent Information
- Application Number
- CN202411543423.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively utilize titanium-containing blast furnace slag, and the traditional photocatalytic CO2 conversion technology has problems such as low conversion rate, harsh reaction conditions and poor thermal stability of the catalyst.
By crushing, grinding and acid-base combined leaching of titanium-containing blast furnace slag, perovskite photocatalytic materials with crystal-branched structures are prepared, and microwave baking technology is used to regulate the energy structure of the material to improve its photocatalytic properties.
Efficient CO2 photocatalytic reduction is achieved, the yields of CO and CH4 are significantly improved, and the materials have good environmental performance and high recovery.
Smart Images

Figure CN119524829A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste resource utilization, and specifically refers to a method for preparing perovskite photocatalytic reduction material by using titanium-containing blast furnace slag. Background Art
[0002] Titanium resources are mainly found in the form of polymetallic symbiotic vanadium-titanium magnetite. After years of production practice and research, a mature process of mineral processing-blast furnace smelting separation and recovery of titanium and iron has been formed. About 53% of the TiO2 in the original ore is enriched in the blast furnace slag in the form of ilmenite, perovskite, and diopside after blast furnace smelting, and its TiO2 content can reach more than 20%. At present, the stockpile of titanium-containing blast furnace slag is huge and is still growing at a relatively high rate. If the valuable components in the titanium-containing blast furnace can be cleanly and efficiently utilized as resources, it will not only greatly alleviate the contradiction between the supply and demand of titanium resources, but also have important significance for environmental protection.
[0003] At present, the methods for resource utilization of titanium-containing blast furnace slag are mainly divided into stabilization solidification method, acid leaching method, activation roasting-acid leaching method, carbonization-chlorination method, molten salt electrolysis method, metallurgical modification-selective precipitation method, etc. In comparison, the metallurgical modification-selective precipitation method is an important way to achieve efficient utilization of titanium-containing blast furnace slag by strengthening the directional enrichment and separation of titanium-containing components to a single mineral phase based on the characteristics of dispersed titanium-containing components and complex mineral phase structure in titanium-containing blast furnace slag.
[0004] Carbon dioxide, as a greenhouse gas, is the main cause of global warming. CO2 emissions mainly come from the combustion of fossil fuels such as coal in industrial production processes. Therefore, in order to reduce CO2 emissions, it is still necessary to develop efficient CO2 capture and conversion technologies on the basis of developing low-carbon energy, promoting energy-saving technologies, and realizing the transformation and upgrading of energy infrastructure from the source. Compared with traditional thermal catalytic CO2 conversion technology, which has low conversion rate, harsh reaction conditions and poor thermal stability of catalysts, photocatalytic reduction technology can efficiently convert CO2 into hydrocarbon oxides with economic value, and has important development prospects.
[0005] Perovskite has structural characteristics such as large specific surface area and a variety of oxidized metal ions, and has broad application prospects in the field of catalysis. Soltani T, Zhu X, Yamamomo A et al. published a document entitled "Effect of transition metal ox-ide cocatalyst on the photocatalytic activity of Ag loaded CaTiO3 for CO2 reduction with water and water splitting" in Applied Catalysis, B: Environmental in 2021. A dual cocatalyst composed of silver and transition metal oxides was loaded on the surface of CaTiO3, and H2O was used as an electron donor for photocatalytic reduction of CO2. The CO generation rate can reach 7.31 μmol / h. However, the dual cocatalyst loading process has high requirements on the experimental conditions. Once the active components agglomerate, the catalytic performance will drop significantly. Therefore, it is necessary to evenly disperse the two additives on the carrier surface and strictly control the particle size. Lin JJ, Hu JS, Qiu CW et al. published a paper titled "In-situ hydrothermal etching fabrication of CaTiO3 on TiO2 nanosheets with heterojunction effects to enhance CO2 adsorption and photocatalytic reduction" in Catalysis Science & Technology in 2019. They proposed to use saturated calcium hydroxide solution to simply in-situ hydrothermal etching of titanium dioxide nanosheets to synthesize CaTiO3 / TiO2 compact heterostructure photocatalysts, which greatly enhanced the photocatalytic reduction of CO2, and the CO generation rate was 5.6 times that of TiO2. Due to the disadvantages of perovskite such as high energy band gap and high probability of recombination of photogenerated electrons and holes, the activity of CaTiO3 in photocatalytic reduction needs to be effectively improved by ion doping, compounding with other semiconductors, and introducing defects. This technical process is complicated, and the preparation process uses a large amount of acid and alkali, which is easy to cause secondary pollution to the environment.
[0006] Based on this, the applicant considered providing a method for preparing a CO2 photocatalytic reduction material, so as to realize the resource utilization of titanium-containing blast furnace slag while producing the CO2 photocatalytic reduction material. Summary of the invention
[0007] In order to overcome the shortcomings of the above-mentioned technology, the purpose of the present invention is to provide a method for preparing perovskite photocatalytic reduction material from titanium-containing blast furnace slag, which solves the problem of resource utilization of titanium-containing blast furnace slag and prepares a CO2 photocatalytic reduction material with the advantages of good catalytic performance and environmental protection.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing perovskite photocatalytic reduction material from titanium-containing blast furnace slag comprises the following steps:
[0010] 1) taking titanium-containing blast furnace slag, crushing, grinding and filtering in sequence, then taking the filter cake, drying it, and obtaining dried slag;
[0011] 2) taking the dried slag, performing microwave roasting, and then cooling it with the furnace to obtain microwave roasted slag;
[0012] 3) crushing and grinding the microwave roasted slag, and then subjecting it to an acid-base combined leaching treatment to obtain a perovskite photocatalytic reduction material.
[0013] Preferably, in the titanium-containing blast furnace slag, the weight percentage of TiO2 is 6-25%, and the weight percentage of CaO is 22-38%.
[0014] Further preferably, in the titanium-containing blast furnace slag, the weight percentage of SiO2 is 22-32%, the weight percentage of Al2O3 is 12-19%, the weight percentage of MgO is 7-11%, the weight percentage of Fe2O3 is 0.2-3.8%, and the weight percentage of V2O5 is 0.2-0.5%.
[0015] Preferably, the perovskite has a branched structure.
[0016] Preferably, in the perovskite, the content of CaTiO3 is ≥80wt%, and the aspect ratio of the branched perovskite is 5 to 10. The optical band gap (2.25eV) of the branched perovskite is lower than that of the amorphous perovskite (3.5eV), and it has a response characteristic to visible light, so that the branched perovskite has better photocatalytic performance.
[0017] Preferably, in the method, the recovery rate of titanium is ≥80wt%. The photocatalytic reduction material has a high content of CaTiO3 active components, a special branched crystal structure, and a recovery rate higher than that of a traditional sorting process.
[0018] Preferably, in the crushing process of step 1), the titanium-containing blast furnace slag is subjected to coarse crushing, medium crushing and fine crushing in sequence; after fine crushing, the particle size <-45 μm is not less than 90wt%, thereby reducing the wear on the crusher in the subsequent crushing process.
[0019] Further preferably, in the crushing process of step 1), the titanium-containing blast furnace slag is coarsely crushed by a jaw crusher, medium crushed by a roll crusher, and finely crushed by a ball mill. The crushing process can increase the contact area between the blast furnace slag and the reaction gas, promote the chemical reaction during the roasting process, and help further extraction of titanium.
[0020] Preferably, in the grinding process of step 1), the crushed titanium-containing blast furnace slag is ground to a -200 mesh with a content of more than 90 wt%.
[0021] Preferably, step 2) further comprises adjusting the basicity of the drying slag to 0.8-1.0 by using calcium oxide and / or silicon dioxide before microwave roasting; the enrichment and growth of perovskite are promoted by adjusting the basicity.
[0022] Preferably, the parameters of the microwave roasting are as follows: initial temperature is 20-30°C; heating rate is 15-25°C / min, microwave heating temperature is 1100-1300°C, and heating time is 30-80min. Microwave heating to 1100-1300°C can heat the titanium-containing blast furnace slag to complete melting, and the heating temperature is lower than the roasting temperature (1300-1500°C) of the titanium-containing blast furnace slag in the muffle furnace, which reduces the energy consumption of the process.
[0023] Preferably, in the grinding process in step 3), the crushed microwave roasted slag is ground to <-74 μm and not less than 90wt%, and then filtered and the filtered residue is dried; the surface area of the blast furnace slag is increased, so that the leaching solution is more easily in contact with the titanium component in the blast furnace slag, thereby improving the leaching rate of titanium.
[0024] Preferably, the acid-base combined leaching treatment in step 3) comprises the following steps: heating the microwave roasted slag filter residue after the drying treatment to 85-95° C. with acid solution, keeping the temperature and leaching for 2.5-3.5 hours; and then leaching in alkaline solution at 28-35° C. for 0.5-1.5 hours. The reaction temperature and reaction time are lower than those of the general blast furnace slag leaching process, reducing the energy consumption of the process flow.
[0025] Further preferably, the acid solution includes any one of HCl solution, H2SO4 solution, and HF solution, and the concentration of the acid solution is 5-7 mol / L; the alkali solution includes any one of NaOH solution and KOH solution, and the concentration of the alkali solution is 0.5-1.5 mol / L. The acid and alkali concentrations used are lower than those in the general blast furnace slag leaching process, which reduces costs and reduces environmental damage.
[0026] Further preferably, the acid-base combined leaching treatment in step 3) includes: heating the dried microwave-roasted slag after the grinding treatment to 90°C with a 6 mol / L HCl solution, keeping warm and leaching for 3 hours, naturally cooling, filtering, and taking the filter residue; then heating the filter residue to 30°C in a 1 mol / L NaOH solution, keeping warm and leaching for 1 hour, filtering, and taking the filter residue to obtain the perovskite photocatalytic reduction material.
[0027] The present invention also provides a perovskite photocatalytic reduction material prepared by the above method; the perovskite has a branched structure with an aspect ratio of 5 to 10; the chemical composition of the perovskite includes CaTiO3, and the content of CaTiO3 is ≥80wt%.
[0028] The present invention also provides an application of a perovskite photocatalytic reduction material in a CO2 photocatalytic reduction reaction, wherein the perovskite photocatalytic reduction material is the perovskite photocatalytic reduction material prepared by the above method or the above perovskite photocatalytic reduction material.
[0029] The present invention also provides a CO2 photocatalytic reduction method, comprising the following steps: mixing a photocatalyst with deionized water and coating the mixture on the bottom of a reactor, then injecting CO2 into the reactor, and performing photocatalytic reaction under light in a closed environment to obtain CO and CH4; the photocatalyst is the perovskite photocatalytic reduction material prepared by the above method or the above perovskite photocatalytic reduction material; the CO yield is ≥8.12 μmol·g -1 , CH4 yield ≥ 2.13 μmol·g -1 .
[0030] Further preferably, the CO2 photocatalytic method comprises the following steps: performing photocatalytic reduction of CO2 in a closed quartz reactor. A 300W incandescent lamp with an AM 1.5 filter is used as the light source, and the light intensity is 200mW / cm 2 More specifically, the photocatalyst is mixed with deionized water at a mass ratio of 3.5 to 4.5:1 and then coated on the bottom of the reactor. Before the reaction, CO2 is injected into the reactor until the volume of CO2 and the mass ratio of the photocatalyst are 7 to 8:1. Thereafter, light induced reaction occurs to generate CO and CH4, and the chemical reaction formula is as follows: 3CO+2H2O→CH4+2CO+3O2.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention uses titanium-containing blast furnace slag as raw material, extracts and prepares perovskite catalytic material from solid waste, and uses it for CO2 photocatalytic reduction, thereby providing an effective way to realize high-value utilization of solid waste.
[0033] The preparation of the perovskite photocatalytic material of the present invention realizes the regulation of the energy-changing structure of the perovskite by a microwave external field, and the catalytic material has visible light response and good CO2 catalytic reduction performance.
[0034] The catalytic material prepared by the present invention greatly reduces the consumption of raw materials such as rare and precious metals in the process of modification and compounding of perovskite-type catalytic materials, thereby reducing the cost of raw materials.
[0035] The perovskite photocatalytic reduction material of the present invention has a high yield of CO and CH4 in the process of CO2 photocatalytic reduction, which is 0.52 times and 2.18 times that of the commercially available calcium titanate reagent. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is the XRD diagram of the perovskite photocatalytic material obtained in Example 2 of the present invention.
[0037] Figure 2 This is an electron microscope image of the perovskite photocatalytic material obtained in Example 2 of the present invention.
[0038] Figure 3 is a UV-visible diffuse reflectance spectrum of the perovskite photocatalytic material obtained in Example 2 of the present invention;
[0039] Figure 4 It is a graph showing the yield of CO and CH4 generated by the photocatalytic reduction of CO2 using the perovskite photocatalytic material and calcium titanate reagent obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0040] In order to better explain the present invention, the main contents of the present invention are further explained below in conjunction with the drawings and specific embodiments, but the contents of the present invention are not limited to the following embodiments.
[0041] The main components of the titanium-containing blast furnace slag raw materials in Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1.
[0042] Table 1: Weight percentage of main components of titanium-containing blast furnace slag
[0043]
[0044] Example 1
[0045] A method for preparing perovskite CO2 photocatalytic reduction material using titanium-containing blast furnace slag as raw material comprises the following steps:
[0046] 1) Raw material processing: Take titanium-containing blast furnace slag, crush, grind and filter in sequence, then take the filter cake, dry it, and obtain dried slag with a basicity of 0.9; the crushing process uses a jaw crusher for coarse crushing, a roll crusher for medium crushing, and a ball mill for fine crushing to a particle size of <-45μm, which is 90wt%. Grind to -200 mesh, which is 90wt%.
[0047] 2) 16 g of dried slag with a basicity of 0.9 was placed in a microwave muffle furnace for microwave roasting, and then cooled with the furnace to obtain microwave roasted slag; the parameters of the microwave roasting were as follows: the initial temperature was 25°C; the heating rate was 20°C / min, the microwave heating temperature was 1200°C, and the heating time was 60 min.
[0048] 3) crushing and grinding the cooled microwave roasted slag, then filtering, drying the filter residue, and then leaching the filter residue by acid-base combination to obtain perovskite; during the grinding process, the crushed slag is ground to <-74μm, which is 90wt%. The acid-base combination leaching includes: heating the dried grinding filter residue to 90°C with a 6mol / L HCl solution for leaching for 3h, naturally cooling, filtering the filter residue, and then heating the filter residue to 30°C in a 1mol / L NaOH solution for leaching for 1h, filtering the filter residue and drying it to obtain the perovskite photocatalytic reduction material.
[0049] In the above method, the recovery rate of titanium is 84.3%, and the content of CaTiO3 in the obtained perovskite photocatalytic reduction material is 81.02%, and the aspect ratio of the crystal branch structure is 6-7.
[0050] The obtained perovskite photocatalytic reduction material is used for photocatalytic reduction of CO2, as follows:
[0051] The photocatalytic reduction of CO2 was carried out in a 150 ml sealed quartz reactor. A 300 W incandescent lamp with an AM 1.5 filter was used as the light source, and the light intensity was 200 mW / cm 2 .
[0052] More specifically, 20 mg of the perovskite photocatalyst prepared in this example was coated on the bottom of the reactor together with 5 ml of deionized water. Before the reaction, high-purity CO2 was injected into the reactor until its saturation value. Thereafter, a photoinduced reaction occurred, and the gaseous products were collected with a syringe and analyzed by gas chromatography. The concentration of CO(CH4) at different reaction times was then calculated to measure the catalytic efficiency. The results are as follows: the yields of CO and CH4 were 8.12 μmol·g -1 and 2.13 μmol·g -1 .
[0053] Example 2
[0054] The difference between this embodiment and embodiment 1 is that in step 2), the basicity of the dried slag is adjusted to 0.8 by adding 0.512 g of silicon dioxide and 19.488 g of titanium-containing blast furnace slag to 16 g of dried slag with a basicity of 0.9.
[0055] The perovskite photocatalytic reduction material obtained in this example was tested and analyzed, and the analysis results are as follows: Figures 1 to 3 shown.
[0056] Depend on Figure 1 From the XRD diagram, we can see that the main component of the perovskite photocatalytic material extracted from titanium-containing blast furnace slag is CaTiO3, and the purity of CaTiO3 is relatively high. The characteristic diffraction peaks of other impurity components are not obvious.
[0057] like Figure 2 As shown, it can be seen from the electron microscope results that, compared with the traditional method, the microstructure of the perovskite photocatalytic material obtained by the present invention has a special branched structure, and the newly formed perovskite grains grow densely along the branches, and their aspect ratio is about 8-9.
[0058] like Figure 3 As shown in the UV-visible diffuse reflectance spectrum, the band gap (2.25 eV) of the perovskite catalytic material obtained in the present invention is significantly lower than that of the calcium titanate reagent (3.5 eV) (Enhui Jiang Lili Yang et al., 2020, published in the Journal of Colloid and Interface Science, "Multi-shelled hollow cube CaTiO3 decorated with Bi 12 O 17 Cl2 towards enhancing photocatalytic performance under the visible light), and has good photocatalytic activity.
[0059] In this embodiment, the recovery rate of titanium is 83.6%. In the obtained perovskite photocatalytic reduction material, the content of CaTiO3 is 83.1%, and the aspect ratio of the crystal branch structure is 8-9.
[0060] The obtained perovskite photocatalytic reduction material was used for photocatalytic reduction of CO2, and the perovskite in this embodiment was compared with commercially available calcium titanate for photocatalytic reduction of CO2. The results are shown in FIG. Figure 4 shown.
[0061] like Figure 4As shown in the figure, the CO2 photocatalytic reduction performance of the perovskite photocatalytic material obtained in this example and the commercially available calcium titanate reagent is good. The CO and CH4 yields of the perovskite photocatalytic material are 8.42 μmol·g -1 and 2.86 μmol·g -1 , which are 0.52 times and 2.18 times of pure CaTiO3 respectively.
[0062] Example 3
[0063] The difference between this embodiment and embodiment 1 is that in step 2), the microwave heating time is 30 minutes.
[0064] In this embodiment, the recovery rate of titanium is 80.1%, the content of CaTiO3 in the obtained perovskite photocatalytic reduction material is 82.2%, and the aspect ratio of the branch structure is 5-6.
[0065] The obtained perovskite photocatalytic reduction material was used for photocatalytic reduction of CO2, CO and CH4 with a yield of 8.21 μmol·g -1 and 2.63 μmol·g -1 .
[0066] Example 4
[0067] The difference between this embodiment and embodiment 1 is that in step 2), the microwave heating temperature is 1100°C.
[0068] In this embodiment, the recovery rate of titanium is 82.5%. In the obtained perovskite photocatalytic reduction material, the content of CaTiO3 is 81.6%, and the aspect ratio of the branch structure is 5-6.
[0069] The obtained perovskite photocatalytic reduction material was used for photocatalytic reduction of CO2, CO and CH4 with a yield of 8.15 μmol·g -1 and 2.47 μmol·g -1 .
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 2 is that in step 2), the microwave heating temperature is 1000°C.
[0072] In this comparative example, the blast furnace slag was not completely melted, and the goal of enriching the titanium component and forming branched perovskite was not achieved.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 2 is that in step 2), the basicity of the dried slag is adjusted to 0.7 by calcium oxide.
[0075] In this comparative example, the recovery rate of titanium is 83.6%, and the content of CaTiO3 in the obtained perovskite photocatalytic reduction material is 85.7%, but the perovskite phase is still amorphous and branched perovskite is not formed.
[0076] The obtained perovskite photocatalytic reduction material was used for photocatalytic reduction of CO2, CO and CH4 with a yield of 7.24 μmol·g -1 and 1.05 μmol·g -1 Its catalytic effect is obviously lower than that of the perovskite catalytic material produced by the method of the present invention.
[0077] In summary, the microwave treatment temperature must exceed 1100°C to melt the titanium slag and form a branched perovskite structure. The optical band gap of the branched perovskite (2.25eV) is lower than that of the amorphous perovskite (3.5eV), which makes the branched perovskite have better photocatalytic performance; in the range of 1100-1300°C, the higher the microwave setting temperature, the better the formation of the branched structure perovskite; in the range of 30-60min, the longer the microwave insulation time, the better the formation of the branched structure perovskite; in the range of alkalinity of 0.8-1.0, a perovskite with a clear branched structure can be formed, among which when the alkalinity is 0.8, the formation of branched perovskite is the best, and when the alkalinity is 0.7 and 1.1, the formation of amorphous perovskite is more obvious.
Claims
1. A method for preparing perovskite photocatalytic reduction material from titanium-containing blast furnace slag, characterized in that: The following steps are involved: 1) taking titanium-containing blast furnace slag, crushing, grinding and filtering in sequence, then taking the filter cake, drying it, and obtaining dried slag; 2) taking the dried slag, performing microwave roasting, and then cooling it with the furnace to obtain microwave roasted slag; 3) crushing and grinding the microwave roasted slag, and then subjecting it to an acid-base combined leaching treatment to obtain a perovskite photocatalytic reduction material.
2. The method according to claim 1, characterized in that: The perovskite has a branched structure.
3. The method according to claim 1, characterized in that: In the perovskite, the content of CaTiO3 is ≥80wt%, and the aspect ratio of the branched perovskite is 5-10.
4. The method according to claim 1, characterized in that: The recovery rate of titanium is ≥80wt%.
5. The method according to claim 1, characterized in that: During the crushing process in step 1), the titanium-containing blast furnace slag is subjected to coarse crushing, medium crushing and fine crushing in sequence; after fine crushing, the particle size <-45 μm is not less than 90 wt%.
6. The method according to claim 1, characterized in that: In step 2), before microwave roasting, the basicity of the dried slag is adjusted to 0.8-1.0 by calcium oxide and / or silicon dioxide; the parameters of the microwave roasting are as follows: the initial temperature is 20-30°C; the heating rate is 15-25°C / min, the microwave heating temperature is 1100-1300°C, and the heating time is 30-80min.
7. The method according to any one of claims 1 to 6, characterized in that: In the grinding process in step 3), the crushed microwave roasted slag is ground to <-74μm and not less than 90wt%, and then filtered and the filter residue is dried; the acid-alkali combined leaching treatment includes the following steps: heating the microwave roasted slag after the drying treatment to 85-95°C with acid solution, keeping it warm and leaching it for 2.5-3.5h; and then leaching it in alkali solution at 28-35°C for 0.5-1.5h.
8. A perovskite photocatalytic reduction material, characterized in that: Prepared by the method described in any one of claims 1 to 7; the perovskite has a branched structure with an aspect ratio of 5 to 10; the content of CaTiO3 in the perovskite is ≥80wt%.
9. Application of a perovskite photocatalytic reduction material in a CO2 photocatalytic reduction reaction, characterized in that: The perovskite photocatalytic reduction material is the perovskite photocatalytic reduction material prepared by the method according to any one of claims 1 to 7 or the perovskite photocatalytic reduction material according to claim 8.
10. A method for photocatalytic reduction of CO2, characterized in that: The following steps are involved: The photocatalyst is mixed with deionized water and coated on the bottom of the reactor, CO2 is then injected into the reactor, and a photocatalytic reaction is carried out under light in a closed environment to obtain CO and CH4; the photocatalyst is the perovskite photocatalytic reduction material prepared by the method according to any one of claims 1 to 7 or the perovskite photocatalytic reduction material according to claim 8; the CO yield is ≥8.12 μmol·g -1 , CH4 yield ≥ 2.13 μmol·g -1 .